FORMULATING DESIGN GUIDELINES FOR AN IMMERSIVE VIRTUAL REALITY ENVIRONMENT IN MUSLIM FUNERAL MANAGEMENT EDUCATION IN MALAYSIA (Journal of Creative Industry and Sustainable Culture, 2024)
In Malaysia, Islamic funeral rites hold deep cultural and religious significance. Upon a person's passing, specific rituals rooted in Islamic traditions are observed. However, despite the importance of these practices, many students especially teenagers in Malaysia lack of knowledge and understanding about Islamic funeral management and practices. A preliminary study conducted among 27 teenagers aged 21 to 25 from Universiti Utara Malaysia (UUM) revealed significant gaps in understanding key aspects such as Taharah (ritual washing), Solat Jenazah (funeral prayer), and Kafan (shrouding). This lack of knowledge could have implications for the preservation and practice of Islamic traditions within younger generations. With the rapid integration of digital technologies, there is need to find alternative way, and this refer to the utilization of Immersive Virtual Reality (IVR) Technology in addressing this problem. To bridge this gap, the study proposes formulating design guidelines for an IVR environment focused on Islamic funeral management education in Malaysia. This research aligns with Sustainable Development Goal 4 (SDG 4) by promoting quality education through digital innovation. The objectives include identifying core components for the IVR environment, developing comprehensive design guidelines, and validating these guidelines through expert review. The study employs the Design Science Research Methodology (DSRM), encompassing stages such as awareness, suggestion, development, evaluation, and conclusion. The significance lies in exploring innovative, interactive approaches for teaching Islamic funeral practices, offering an immersive learning experience that enhances student engagement, comprehension, and retention. Ultimately, this research contributes to the development of IVR applications that support effective, technology-based education in alignment with the MADANI Economy vision.